Status, Needs, and Perspectives on the Practice of Endourology in Africa: a Continental Survey of 21 Reference Centers - Saleh Abdelkerim Nedjim; Ziba Ouima Justin Dieudonné; Hagguir Hissein; Kaleab Habtemichael Gebreselassie; Douglas Arthur; Mahamane Salissou; Mahamat Ali Mahamat; Abdullahi Khalid; Emmanuel Muhawenimana; Cléhaude Dibingue; Thoto Shabani Marebo; Gnimdou Botcho; et al. (Société Internationale d’Urologie Journal)
Endourology occupies an important place in modern urological practice. Compared with conventional surgery, it offers improved safety and patients experience less severe postoperative effects. Its use requires a certain level of equipment and technical skills. In many developed countries, it has been established for years and its practice has become routine. In Africa, it is still not very practical or even non-existent in certain reference centers. This survey conducted among the heads of urology departments or training coordinators in African referral centers defines the current practice of endourology. According to the needs and perspectives identified, it is important, if not essential, to create services or reference centers specializing in endourology. The role of these centers will be to take care of patients and train urologists in technical skills. The creation of a sub-regional and international network could contribute to the development of this practice. Multi-stakeholder cooperation (inter-state, with non-governmental organizations, companies or corporations) is also necessary.